The Guardians [videorecording (DVD)] - Beauvois, Xavier; Baye, Nathalie, 1948-; Smet, Laura, 1983-; Bry, Iris; Pérochon, Ernest, 1885- (Music Box Films, 2018)
An affecting human drama of love, loss, and strength unfolds against the backdrop of World War I. The women of the Paridier farm, under the deft hand of Hortense, the family's matriarch, must grapple with the workload while the men are off at the front. New tools allow the women to triumph over the land, newfound independence is acquired, yet emotions are stirred, especially when the men return.